Tjälinventeringsprojektet : en jämförande studie av tjälinventeringar gjorda av olika aktörer - Berglund, Andreas (Luleå tekniska universitet, Geoteknologi, 2010)
Roads are affected by frost. For maintenance and action planning of these roads, a well performed inventory is a necessary base. It will also be a base for priority of different objects for repair and maintenance. Therefore, it is very important to have a similar ground for the judgment. This can be difficult to achieve as different companies and persons are enrolled different years due to type of contract used, capacity, experience, knowledge etc. In a pre-study great differences were found when comparing two inventories done on the same road in year 2008 and 2009. The question was then raised, if the provided information on how to perform an inventory was good enough in order to carry out a high quality work. Another question raised, was if the differences really are that obvious between different persons performing the inventory.The method used for the study was to have four actors to carry out an inventory each on the same road, at the same time, and then compare the obtained results. The actors were "Konsult A" and B, Swedish Transport Association (TV) and persons from Luleå University of Technology (LTU). Ranked in order of practical experience the most experienced was Konsult B, then Konsult A, TV and LTU. The road studied was AC805 Lidbacken to Femvägaskälet. It is situated outside Skellefteå in the county of Västerbotten in the north part of Sweden. The total length of the studied road was about 15 km and it has an ADT of 576. Four sections, which represented the road as a whole and also showed the main differences and similarities, were closer analyzed. One section focused on an overview, one on cracks and two sections focused on bumps and roughness. In the report, the results from the four inventories are presented graphically in order to give the reader an overview and a chance to comparison. The results show that there are both great differences and similarities between the four inventories. The two most experienced, Konsult A and Konsult B had about the same percentage of their total crack length ...